Measuring the Social Sustainability of Urban Communities: The Role of Local Authorities - Bogdana NEAMŢU (Transylvanian Review of Administrative Sciences, 2012)
The paper explores the topic of social sustainability which in the last years has attracted interest from both the academia and political decision-makers and analyzes emerging issues on the social sustainability agenda such as urban governance, citizens’ empowerment and participation, sense of place, urban livability etc. The article focuses on how social sustainability of a community can be evaluated: it looks at existing methodologies, metrics and tools and uses the indicators from the Egan report (UK) to illustrate the shifts currently taking place in the realm of sustainability assessment. The empirical research strives to determine whether public servants working in urban planning or in other areas that are closely related to planning are in favor of introducing at the local level a sustainability assessment system (research carried out in medium and large municipalities from the North-Western region of Romania). The main conclusion which can be derived from both literature and practice is that the themes under the umbrella of social sustainability are changing and that sustainability assessment is currently in the process of being better understood and used at the local level.